Sustainable Bioremediation of Lipid-Rich Wastewater Using a Lipase from Penicillium rubens LBM 081 - Ortellado, Laura Ester (2025)
The improper discharge of wastewater has increased the presence of pollutants,among which lipids are particularly problematic. These compounds form oily layers thathinder oxygen transfer and sunlight penetration, negatively impacting aquatic ecosystems.Conventional methods for treating such effluents are often costly and environmentallyunfriendly. In this context, bioremediation using lipases, such as those produced byPenicillium rubens LBM 081, represents an effective and sustainable alternative. This studyevaluated the biotechnological potential of the lipase from P. rubens LBM 081 for the hydrolysisof lipid-rich wastewater. Lipase activity was influenced by the carbon and nitrogensources in the culture medium, reaching maximum activity (2780 U mL⁻1) under optimalconditions of 2% meat peptone, 4% olive oil, a spore concentration of 1 × 106, incubationat 30 °C, and agitation at 140 rpm. The optimized enzymatic supernatant significantlyreduced COD, oils, and total fats in the effluents. Furthermore, GC-MS analysisrevealed a significant increase in free fatty acids, confirming triglyceride hydrolysis. Theseresults highlight the potential of P. rubens LBM 081 lipase as an effective and environmentallysustainable biotechnological alternative for the treatment of lipid-rich wastewater.